2020
DOI: 10.1186/s12879-020-4934-y
|View full text |Cite
|
Sign up to set email alerts
|

Rabies in Uganda: rabies knowledge, attitude and practice and molecular characterization of circulating virus strains

Abstract: Background: Rabies is a deadly preventable viral disease that affects all warm-blooded animals and widespread in many regions including Africa. The disease remains of major public health importance in Uganda. The purpose of this study was to establish Knowledge, Attitude, Practice (KAP) of Rabies in Moyo and Ntoroko districts and to characterize Rabies virus (RABV) strains from seven districts of Uganda with consistent prevalence of rabies. Methods: KAP survey data were collected based on animal biting history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 20 publications
4
17
2
1
Order By: Relevance
“…Our results showed that 49% of the respondents within the HMP were pet owners (owning a cat, a dog or a combination of the two). This level of pet ownership was similar to what was observed in other studies in Africa, where pet ownership was reportedly between 40% and 58% [ 17 19 ]. Within the pet owner sub-population specifically, 60% of the respondents within the HMP reported taking their pet(s) to a veterinary office.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results showed that 49% of the respondents within the HMP were pet owners (owning a cat, a dog or a combination of the two). This level of pet ownership was similar to what was observed in other studies in Africa, where pet ownership was reportedly between 40% and 58% [ 17 19 ]. Within the pet owner sub-population specifically, 60% of the respondents within the HMP reported taking their pet(s) to a veterinary office.…”
Section: Discussionsupporting
confidence: 91%
“…While respondents in our study were never specifically asked whether they had their pets vaccinated at any point in time, these observations would suggest that approximately 43% of the owned dog population should theoretically have received their annual vaccination against rabies every year. Assuming this to be accurate, the results would be similar to findings from Uganda [ 17 ] and Kenya [ 21 ] where a low percentage of respondents (between 35% and 43%) reported having their pets vaccinated against rabies, and in contradiction to findings from Nigeria [ 18 ], Ethiopia [ 19 ] and Rwanda [ 20 ] where a much higher percentage of respondents (between 74% and 94%) reported having their pets vaccinated against rabies. Furthermore, this speculative vaccination coverage in the HMP (30%) is well below the recommended vaccination coverage of 70% [ 1 ], which could explain the persistence of the disease in the province.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…A more recent KAP survey conducted in the Mbale district of Uganda concluded that of the survey respondents, only 44% has sufficient knowledge of rabies, and authors suggest that, even currently, more educational awareness regarding rabies is needed in Mbale [ 27 ]. Findings from another recent KAP survey conducted in the Moyo and Ntoroko districts of Uganda suggest that dog bites are still high, with 75% and 62.5% of respective bite rates [ 28 ]. Also, in East Africa, a 2015 KAP study from Ethiopia reports a bite rate of 42% among survey respondents [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within samples submitted for rabies diagnosis, those of cattle, goats, sheep, and horses showed a higher percentage of positivity than dog and cat ones [26]. In Namibia, cattle rabies cases are second to dogs during 2011-2017 [50], also in Uganda during 2011-2013 [16]. In South Africa, rabies has been mainly diagnosed in dogs (52%), followed by (34%) cattle [51].…”
Section: Epidemiologymentioning
confidence: 99%